Spain : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that with growth proceeding at a steady pace of 2.6 percent during 2004, the Spanish economy has weathered the slowdown in the European Union relatively well. The external current account is estimated to have widened to some 4u percent of GDP in the first half of 2004. A gradual, but sustained recovery is expected, with GDP growth projected at 2.7 percent in 2005-again based on the strength of domestic demand, with a continued negative contribution of net exports.